2021
DOI: 10.1016/j.colcom.2020.100342
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected observation of an intermediate hexagonal phase upon fluid-to-gel transition: SDS self-assembly in glycerol

Abstract: Understanding morphological transformations upon temperature-induced mesophase transitions offers mechanistic insights into the self-assembly process. We have recently reported the unexpected formation of a microfibrillar lamellar gel in SDS-glycerol mixtures above a critical gelation concentration (CGC) as low as ~2 wt%. The gel phase comprised a fibrillar structure on the microscale and a lamellar structure on the nanoscale. Here, the nanoscopic structure of the gel as a function of temperature was probed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Previous studies into the SDS in the glycerol system demonstrated a fibrillar structure on the microscale, with a lamellar nanostructure; the d -spacing of this phase was determined to be d = 5.56 nm. The gel phase is proposed to form as a result of the entanglement of the microfibrils, entrapping free glycerol and increasing the viscosity.…”
Section: Results and Discussionmentioning
confidence: 91%
“…Previous studies into the SDS in the glycerol system demonstrated a fibrillar structure on the microscale, with a lamellar nanostructure; the d -spacing of this phase was determined to be d = 5.56 nm. The gel phase is proposed to form as a result of the entanglement of the microfibrils, entrapping free glycerol and increasing the viscosity.…”
Section: Results and Discussionmentioning
confidence: 91%
“…For instance, in Matthews et al, the decreasing entropy and increasing bulk viscosity in the presence of glycerol were discussed as the main mechanisms for the unexpected formation of a microfibrillar gel in SDS and glycerol mixtures at a critical gelation concentration. 33 Also, Kulmyrzaev et al showed a decrease in protein aggregation rate and gelation that was suggested by the increase in the viscosity. 34 On the other hand, glycerol is known to stabilize the native structure of proteins and peptides, thus changing their hydration and aggregation rate.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…In our experiment, the concentration of glycerol was 70%, and the viscosity increased 20-fold at room temperature, so the diffusion of peptides and their aggregation slowed down strongly. For instance, in Matthews et al ., the decreasing entropy and increasing bulk viscosity in the presence of glycerol were discussed as the main mechanisms for the unexpected formation of a microfibrillar gel in SDS and glycerol mixtures at a critical gelation concentration . Also, Kulmyrzaev et al showed a decrease in protein aggregation rate and gelation that was suggested by the increase in the viscosity …”
Section: Resultsmentioning
confidence: 99%
“…However, the nanoscopic structure underlying such a macroscopic phase transition was not clear. It has been reported in a related system that, at T > ~ 45 o C, an SDS-in-glycerol gel underwent a lamellar gel-to-fluid transition, with the SDS aggregates transformed from lamellae, via an intermediate hexagonal phase, to cylindrical micelle solutions [18,20].…”
Section: Introductionmentioning
confidence: 99%